Հին հայկական տեղանուններն ու ցեղանունները սեպագիր աղբյուրներում և նրանց պատմական արմատները - Հարությունյան, Նիկոլայ («Զանգակ - 97»)
Numerous Armenian-Assyrian, Armenian-Hittite and Armenian-Urartian toponymical and ethnonymical correspondences (e.g. Alzini — A j'nik, Diauhi — Taykc, Zabaha — avaxkc, upani — Copkc, uluku — uk etc.) revealed in the cuneiform inscriptions of ancient oriental kings describing their military campaigns to the Armenian highland allows us to assume that we deal with Armenian topönyms and ethnonyms reflected in cuneiform and, hence, the population of these teiritories was Armenian. This assumption is corroborated by a number of Akkadian, Hittite and Urartian borrowings in Armenian. It also follows that the main destructive forces that caused the fall of the Urartian kingdom were Armenian tribal unions, the predecessors of the later Armenian State. In che following centuries the Urartian population assimilated gradually to Armenians, thus contributing to the ethnogenetical process of the Armenian nation.
Keywords: Հայոց պատմություն; Ազգագրություն